The chemical and sensorial changes in rainbow trout caviar salted in different ratios during storage - Inanli, Aye Gurel; Coban, Ozlem Emir; Dartay, Murside (Springer Tokyo, 2010)
In this study, the intention was to investigate the chemical and sensorial changes occurring during cold storage (4 +/- 1 degrees C) of caviar obtained from rainbow trout Oncorhynchus mykiss W. 1792 that was dry salted in different ratios. Caviar has a higher fat and protein content than other seafood products, and in processing it with dry salting technology, it was determined that the shelf life could be up to 28 days for the experimental group in which salt was applied at a rate of 4% and up to 35 days for the experimental group in which salt was applied at a rate of 8%. Thus the storage period of the samples is longer for the products to which a high (8%) amount of salt was applied than the products to which a low (4%) amount of salt was applied in the salting process.
Keywords: Caviar; Rainbow trout; Shelf life; Chemical; Sensorial